Influence of Workplace Spirituality and Employee Empowerment on Organizational Citizenship Behavior : An Empirical Study in the Metal Industry - Achary, A. Chiranjibi Rambabu; Mohapatra, Amiya Kumar; Chakrabarti, Deepankar; Mohanty, Debasis; Panda, Rajesh Kumar (Prabandhan: Indian Journal of Management, 2026)
Purpose : The paper aimed to examine the effects of workplace spirituality (WPS) on the organizational citizenship behavior (OCB) and to assess the mediating role of employee empowerment (EE) in the metal manufacturing industry in Odisha, India. Methodology : Data were collected through structured questionnaires using convenience sampling from 515 employees in the metal manufacturing industry between September 2024 and March 2025. Reliability and validity were assessed using Cronbach’s alpha, KMO, Bartlett’s tests, and confirmatory factor analysis. The hypothesized direct and mediating relationships were examined using structural equation modeling (SEM) with IBM AMOS, supported by bootstrapping. Findings : Spirituality at work had a positive and significant influence on the EE and OCB, and empowerment had a positive impact on OCB. The relationship between (WPS) and OCB had an indirect relationship through EE, which is one of the mechanisms that connects the spiritual work environment to discretionary behaviors. Practical Implications : The results indicated that the combination of spiritual values and empowerment practices can facilitate employee engagement, ethical behaviors, and collaboration, and create increasingly inclusive and participative industrial work environments. Originality : The present research offered empirical support of the Indian manufacturing environment, proving EE as the mediating factor between WPS and OCB and supporting the topicality of human-focused management strategies.